2013
DOI: 10.1016/j.jacc.2013.03.032
|View full text |Cite
|
Sign up to set email alerts
|

J-Shaped Association Between QTc Interval Duration and the Risk of Atrial Fibrillation

Abstract: In this large ECG study, a J-shaped association was found between QTc interval duration and risk of AF. This association was strongest with respect to the development of lone AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 41 publications
9
121
0
1
Order By: Relevance
“…Messenger ribonucleic acid expression studies have shown that the expression of important ion channel com- related to an increased incidence of AF. 21, 22 The possible mechanism of QTc predicting AF recurrence after catheter ablation in HCM patients include: (1) atrial myopathy with similar structural and electrophysiological remodeling as the ventricular myopathy. Prolonged atrial action potential duration could induce trigger activity in the atria and then initiate AF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Messenger ribonucleic acid expression studies have shown that the expression of important ion channel com- related to an increased incidence of AF. 21, 22 The possible mechanism of QTc predicting AF recurrence after catheter ablation in HCM patients include: (1) atrial myopathy with similar structural and electrophysiological remodeling as the ventricular myopathy. Prolonged atrial action potential duration could induce trigger activity in the atria and then initiate AF.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, QTc has been associated with the development of AF. 21, 22 It is possible that QTc might also predict the outcome of AF ablation, which has never been reported. The reason we chose a HCM population to test our hypothesis in this pilot study was based on the following understanding: (1) similar pathological changes of atrial and ventricular myocardium in HCM patients; (2) comparing to the general population, QTc prolongation at baseline is much more common in HCM patients regarless of the type of heart rhythm (AF or sinus); and (3) many HCM patients develop AF, but ablation of this arrhythmia in this specific population remains challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is increasing evidence that prolongation of the mean QT interval is associated with AF (330). A recent study including digital ECGs from more than 300,000 persons confirmed that the QTc interval length is a predictive parameter for the susceptibility of AF (308). Of note, both shortened and in particular prolonged QTc interval duration are risk factors for AF (308).…”
Section: Striking the Wrong Note: Genetic Variation Causing Arrhytmentioning
confidence: 99%